The Effect Of Scrapbook Media Education On Increasing Pregnant Women's Knowledge About Exclusive Breast Milk - Hartateana, Ridanna; Sumarni, Sri; Setianingsih, Agustin (Postgraduate Program , Poltekkes Kemenkes Semarang, 2022)
ABSTRACT The low coverage rate of exclusive breastfeeding at the Sayung II Health Center based on data from the Health Profile of Demak Regency in 2020 is 52.8%, influenced by several kinds of factors, one of which is that educational activities about exclusive breastfeeding have not been maximized. Education is an activity that can provide the ability and knowledge to someone or more by learning. Scrapbook is one of the media used for education and entered into 2-dimensional media whose shape is according to the wishes of the maker by sticking technique. This study aims to determine the effect of scrapbook media education on increasing the knowledge of third trimester pregnant women about exclusive breastfeeding in the working area of the Sayung II Health Center. The research design used a quasi-experimental research design and this research design used a pretest-posttest with control group. This research was conducted from March to April 2022. The sampling method used a total sampling technique with a total sample of 48 people. Data analysis used Paired Sample T-test. The results showed that there was an increase in knowledge of pregnant women about exclusive breastfeeding after being given education in both groups. In the intervention group a p-value of 0.000 <0.05 was obtained and the control group obtained a p-value of 0.000 <0.05. The conclusion of this study is that there is an effect of education with scrapbook media on the knowledge of pregnant women about exclusive breastfeeding.